The Pedestal and the Cage: Feminist Mobilization for Equality and Contest for Constitutional Meaning in the United States in the Decades of 1960 and 1970 - Zara, Nicolás Daniel (2022)
This article aims to propose a reframing of certain aspects of feminist mobilization for equality in the United States of America in the decades of 1960 and 1970, considering some elements of social movements theory and democratic constitutionalism. It analyzes the ways in which the feminist movement’s narrative succeeded in permeating in the constitutional culture of the United States, changing through it the meaning of the U.S. Constitution. In doing so, it focuses on the strategies used by legal feminism in constitutional litigation, on the efforts for the sanction of the Equal Rights Amendment (ERA), and on the interactions between both processes. It addresses the recent revival of the ERA, as well as its text’s shortcomings. Finally, based on the analysis carried out in previous sections, it provides some arguments in support of a new alternative to the old ERA.